Paradise Saved: The remarkable story of New Zealand’s wildlife sanctuaries and how they are stemming the tide of extinction - Curtis, Neil (New Zealand Science Review, 2014)
Paradise saved, by Dave Butler, Tony Lindsay and Janet Hunt, is a comprehensive account of sanctuaries of various types, established to try to restore New Zealand to the way it was, before humans messed everything up by introducing species with which the native flora and fauna had trouble competing. It describes attempts to re-establish kiwi, kokako, tui, saddleback, and all their associates, in their original habitats. Success is very much dependent on first removing predators; so much of the story is about eliminating possums, rats, mustelids and other undesirables.